Pola Konsumsi Ikan Pada Balita di Kampong Tanah Bara Kecamatan Gunung Meriah Kabupaten Aceh Singkil - Diana, Diana; Thahir, Muhammad Agam (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Food consumption is one of the factors that directly affect a person’s nutritional status. Fish is a food that provides relatively high animal protein and provides essential unsaturated fatty acids that the human body needs. This study aims to determine the pattern of fish consumption in toddlers which includes the intensity of fish consumption, reasons for consuming fish, age at which fish were started, frequency of eating fish, types of processed fish consumend, and types of fish consumed. The method used is descriptive method. Sampling with random sampling technique using the slovin formula to get 70 respondents. The result of the study show that the intensity in consuming fish does not mean that toddlers always consume fish, there are 70,8% giving toddlers to eat fish because fish has a high nutritional content, toddlers generally consume fish at the age of 1 year as much as 72,2%, and the portion of fish spent at the time of eating the most is 1/2 fish which is 68,9%, as many as 81,1 % of toddlers do not consume processed fish, the type of sea water fish consumed the most is dencis fish namely 54,1%, , the type of fresh water fish consumed the most is nila fish namely 47,3%.Keywords: Comsumption Pattern, Fish, Toddler